2010
DOI: 10.1038/hr.2010.72
|View full text |Cite
|
Sign up to set email alerts
|

Effects of high-intensity aerobic interval training vs. moderate exercise on hemodynamic, metabolic and neuro-humoral abnormalities of young normotensive women at high familial risk for hypertension

Abstract: Exercise training has an important role in the prevention and treatment of hypertension, but its effects on the early metabolic and hemodynamic abnormalities observed in normotensive offspring of hypertensive parents (FH+) have not been studied. We compared high-intensity interval (aerobic interval training, AIT) and moderate-intensity continuous exercise training (CMT) with regard to hemodynamic, metabolic and hormonal variables in FH+ subjects. Forty-four healthy FH+ women (25.0 ± 4.4 years) randomized to co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
167
3
16

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 183 publications
(197 citation statements)
references
References 49 publications
11
167
3
16
Order By: Relevance
“…VO 2max . In contrast, Ciolac et al 33 trained young women with high familial risk of hypertension and found a reduction in PWV after 16 weeks of high-intensity (80 --90% of .…”
Section: Augmentation Indexmentioning
confidence: 91%
“…VO 2max . In contrast, Ciolac et al 33 trained young women with high familial risk of hypertension and found a reduction in PWV after 16 weeks of high-intensity (80 --90% of .…”
Section: Augmentation Indexmentioning
confidence: 91%
“…Estudo no nosso meio demonstrou que a idade não influencia a resposta ao exercício 69 . Outros métodos de treinamento têm sido utilizados como o treinamento complementar de músculos inspiratórios que pode ser indicado naqueles pacientes com IC que apresentam fraqueza da musculatura respiratória (> 70% da pressão inspiratória máxima predita) [70][71][72] ; pilates 73,74 ; treino intervalado e contínuo 66,75,76 ; eletroestimulação 77 ; e hidroterapia 78,79 . Intensidades diferentes de exercício podem ter ação diferente na fisiopatologia da IC 80 .…”
Section: Reabilitação E Treinamento Físico (Tabela 10)unclassified
“…23 More recently, however, high-intensity interval training (HIIT) has raised considerable interest in the clinical context as a potential alternative to MICT for reducing the risk of CVD as well as improving the health and wellbeing outcomes of those affected. [26][27][28][29][30][31][32][33][34] It may be thought that the higher intensity of exercise as with HIIT may increase the risk of an acute cardiovascular event in comparison to MICT. However, HIIT applied in the settings discussed in this paper has been shown to be low risk and is adapted to maintain safety (See safety issues/clinical perspectives section).…”
mentioning
confidence: 99%